Media Audiovisual Efektif Meningkatkan Pengetahuan Tentang Diare Bagi Santriwati Pondok Modern Darussalam Gontor Putri 2 - Nurul Marfu'ah; Rizka Safira; Nadia Saptarina (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
Diarrhea is still one of the main public health problems in Indonesia, proven by the increasing number of diarrhea sufferers from year to year. Diarrhea is often associated with the pesantren environment because the santri live together in the same environment, share the same food, and use the same facilities. Various strategies and efforts have been made to reduce the incidence of diarrhea, one of which is health promotion. This community service program was carried out to determine the effectiveness of counseling with audiovisual methods to increase knowledge about diarrhea in PMDG Female 2 students. This service used a quasi-experimental method with one group pretest-posttest design with a sample of 96 female students. Data were collected using a questionnaire in the form of pretest and posttest, which were then analyzed using a paired T-test with a significance level of 5%. The results of the service implementation showed that the audiovisual counseling method was effective in increasing the knowledge of PMDG Putri 2 students about diarrhea as indicated by (p 0.05) by 14%. This shows that students' level of knowledge increased from good criterion (82%) to very good (96%).